(untitled) (Issues in Social and Environmental Accounting (ISEA), 2012)
This study examines the trend of corporate social responsibility (CSR) disclosures and the role of corporate governance attributes in the CSR disclosures of Shari’ah compliant companies (ShCCs) in Malaysia for the years 2006 and 2009, a period which corresponds before and after a plethora of significant changes in Malaysia, encompassing the recent financial crisis and pol icy changes in the form of corporate governance restructuring. Using a CSR disclosure check list, the extent and quality of CSR discourses of a sample of 76 ShCCs was examined. The results indicate that the extent and quality of CSR disclosures by the ShCCs is in overall low. However, there was a significant increasing trend in both the extent and quality of the CSR disclosures by the ShCCs over time. results of this study offer a number of practical implica tions. First, whilst the findings reveal a significant increasing trend of CSR information subse quent to the policy changes and the recent financial crisis, the CSR information was however not systematically provided, with most of the disclosures being stated in a narrative form. Hence, the policy makers in Malaysia may want to re-enforce the mandatory requirement of CSR information and provide a detailed CSR framework for the companies to follow such as "what" and "how" the CSR information should be disclosed. Second, the role of corporate gov ernance attributes in the social disclosures of the ShCCs did not improve following the revised code, perhaps due to the unfolding recent global financial turmoil which may have undermined the effectiveness of the corporate governance attributes. Finally, this study offers the first em pirical study to have assessed the trend of CSR disclosures and the role of governance attrib utes in CSR disclosure practices by the ShCCs.